2021
DOI: 10.1093/nar/gkab773
|View full text |Cite
|
Sign up to set email alerts
|

Non-canonical LexA proteins regulate the SOS response in the Bacteroidetes

Abstract: Lesions to DNA compromise chromosome integrity, posing a direct threat to cell survival. The bacterial SOS response is a widespread transcriptional regulatory mechanism to address DNA damage. This response is coordinated by the LexA transcriptional repressor, which controls genes involved in DNA repair, mutagenesis and cell-cycle control. To date, the SOS response has been characterized in most major bacterial groups, with the notable exception of the Bacteroidetes. No LexA homologs had been identified in this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…The same occurs in the Moraxellaceae family but the regulator is the UmuDab protein ( Hare et al, 2014 ). In the phylum of Bacteroidetes, the SOS response is regulated by a new peptidase from the S24-family of phage-like repressors which, when derepressed, activates the expression of standard SOS genes ( Sánchez-Osuna et al, 2021 ). The evolution of these peptidases with independent DNA-binding domains once again shows how heterogeneous this response can be.…”
Section: Diversity Of the Sos Response Among Bacterial Speciesmentioning
confidence: 99%
“…The same occurs in the Moraxellaceae family but the regulator is the UmuDab protein ( Hare et al, 2014 ). In the phylum of Bacteroidetes, the SOS response is regulated by a new peptidase from the S24-family of phage-like repressors which, when derepressed, activates the expression of standard SOS genes ( Sánchez-Osuna et al, 2021 ). The evolution of these peptidases with independent DNA-binding domains once again shows how heterogeneous this response can be.…”
Section: Diversity Of the Sos Response Among Bacterial Speciesmentioning
confidence: 99%
“…The repair system found in the IPAC21 genome involves genes that encode the SOS regulon proteins, consisting of three genes that encode the LexA repressor. These genes are a diverse family of bacterial transcription factors that repress genes in the cellular SOS response to DNA damage ( Sánchez-Osuna et al, 2021 ). Furthermore, three genes involved in excision repair for UvrD were found.…”
Section: Resultsmentioning
confidence: 99%
“…Prophage induction is a fundamental process in phage biology and is controlled by the CI protein in phage λ. λ CI is a LexA-like repressor comprised of an NTD involved in DNA binding and repression and a CTD that upon recognition of activated RecA* are autocatalytically separated 17 . CI repressors are present in a wide variety of temperate phage genomes of both Gram-positive and Gram-negative hosts 18 , 19 . Interestingly, several examples of phage CI repressor molecules have been identified that retain some and sometimes even full binding affinities with their cognate promoter DNA after autocatalytic separation of their C- and NTDs 20 23 .…”
Section: Introductionmentioning
confidence: 99%